Functional dysconnectivity within the emotion-regulating system is associated with affective symptoms in major depressive disorder: A resting-state fMRI study. (June 2019) - He, Zongling; Lu, Fengmei; Sheng, Wei; Han, Shaoqiang; Long, Zhiliang; Chen, Yuyan; Luo, Wei; Yu, Yue; Nan, Xiaoyu; Ouyang, Aili; Cui, Qian; Chen, Huafu
Objective: Major depressive disorder (MDD) can be characterized as a multidimensional and system-level disorder. The neuropathophysiological abnormalities have been reported to be distributed in emotion regulation system, involving the prefrontal cortex (PFC), limbic and striatum in convergent studies. Decrease of positive affect and increase of negative affect are recognized as a hallmark of MDD. However, the dysfunctions in affective processing in MDD within the emotion regulation system remains largely unclear. In this study, our goals are to characterize the dysconnectivity pattern within this system and explore the relationships between this kind of dysconnectivity pattern and affective symptoms, which might help us better look into the neuropathophysiological mechanisms underlying MDD. Methods: A total of 34 MDD and 34 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rsfMRI). The alterations in functional connectivity (FC) within the emotion regulation system and their relationships with affective symptoms were explored. Results: Compared with HCs, MDD patients showed aberrant FC within this system. Importantly, deceased FC was mainly involved in the prefrontal–limbic system, while elevated FC was observed in the prefrontal–striatum system. In the MDD group, decreased FC of right posterior hippocampus–left dorsolateral prefrontal cortex (dlPFC) was negatively associated with the negative affect scores and Hamilton Depression Rating Scale scores and the FC of left ventral striatum–left dlPFC was significantly negatively related with the positive affect scores. Conclusions: These findings demonstrated that MDD showed characteristic pathological alterations of the emotion regulation system. Dysconnectivity within prefrontal–limbic system might be more related to the dysregulation of negative affect, whereas dysconnectivity within prefrontal–striatum system might influence more on positive affect processing. The decrease in positive affect and increase in negative affect in MDD might have different pathological basis. These results could help better understand the dysconnectivity pattern in the emotion-regulating system underlying depression.